Influence of Clinical Trial Participation on Subsequent Antithrombin Use - Shah, Bimal R. (Clin Cardiol, 2010)
BACKGROUND: Results from the Superior Yield of the New Strategy of Enoxaparin, Revascularization, and Glycoprotein IIb/IIIa Inhibitors (SYNERGY) trial showed that the low‐molecular‐weight heparin (LMWH) enoxaparin was non‐inferior compared with unfractionated heparin (UFH) in patients with non‐ST‐elevation acute coronary syndromes (NSTE‐ACS) managed invasively. HYPOTHESIS: We explored the influence of SYNERGY trial site participation on subsequent patterns of heparin use for NSTE‐ACS patients treated in routine practice. METHODS: We examined temporal patterns of LMWH use compared with UFH use among 122 764 patients with NSTE‐ACS enrolled in the Can Rapid Risk Stratification of Unstable Angina Patients Suppress Adverse Outcomes with Early Implementation of the ACC/AHA Guidelines (CRUSADE) quality improvement initiative between January 1, 2002 and June 30, 2006, to determine whether site participation in SYNERGY influenced the type of heparin used before and after publication of the SYNERGY results in July 2004. RESULTS: A total of 118 out of 388 (30%) U.S. hospitals participating in CRUSADE simultaneously participated in SYNERGY. SYNERGY sites in the CRUSADE registry were more likely to have a teaching affiliation and have more hospital beds than non‐SYNERGY centers in the registry. There was no difference in the proportion of patients treated with LMWH at SYNERGY and non‐SYNERGY sites prior to July 2004 compared with after July 2004. However, at SYNERGY sites, there was a slight decrease in the proportion of patients treated with both UFH and LMWH within 24 hours of presentation. CONCLUSIONS: The results of the SYNERGY trial did not appear to influence temporal patterns of LMWH use at sites in the CRUSADE registry. Furthermore, site participation in the SYNERGY trial did not alter patterns of LMWH use for NSTE‐ACS after publication of the trial results in July 2004. Copyright © 2009 Wiley Periodicals, Inc.